Cover Image, Volume 529, Issue 13. Issue 13 (9th July 2021) - Rolón‐Martínez, Solymar; Habib, Mohamed R.; Mansour, Tamer A.; Díaz‐Ríos, Manuel; Rosenthal, Joshua J. C.; Zhou, Xiao‐Nong; Croll, Roger P.; Miller, Mark W.
Abstract : The cover image is based on the Research Article FMRF‐NH2‐related neuropeptides in Biomphalaria spp., intermediate hosts for schistosomiasis: Precursor organization and immunohistochemical localization by Solymar Rolón‐Martínez et al., https://doi.org/10.1002/cne.25195 .